KHẢO SÁT TÌNH TRẠNG NHIỄM GIÁP XÁC CHÂN TƠ Octolasmis warwickii NGOẠI KÝ SINH TRÊN GHẸ XANH Portunus pelagicus Ở VÙNG BIỂN KHÁNH HÒA VÀ PHÚ YÊN - Lê, Thị Kiều Oanh; Đặng, Thuý Bình; Trần, Quang Sáng (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
INFESTARION STATUS OF EPIZOIC BARNACLE Octolasmis warwickii ON BLUE SWIMMING CRAB Portunus pelagicus AT KHANH HOA AND PHU YEN PROVINCESThe blue swimming crab, Portunus pelagicus (Linnaeus, 1758), is an economically important species. The presentation of epizoic pedunculate barnacles Octolasmis warwickii may cause difficulties for the growth and development of the host. In this article, we presentthe infestation status of O. warwickii on Portunus pelagicus in different studied areas, males and females and size-groups of crabs. A total of 180 individuals of Portunus pelagicus were examined (90 individuals in Khanh Hoa and 90 individual in Phu Yen included 100 females and 80 males). The results show that the infestation status of O. warwickii on Portunus pelagicus was not significant different between Khanh Hoa and Phu Yen. The prevalence of infestation in female crabs (29%) was significantly higher than in males (12.5%). The infestation varies between size groups; no infection was detected in < 80 mm crabs (both males and females); in female crabs, there was strong positive correlation between the size groups with prevalence (rs = 0.882) and mean intensity (rs = 0.669), while no correlation was observed between male size groups.